PENGARUH KUALITAS PRODUK, LOKASI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE KINOL BISTRO N’POLL DI KOTA PADANG - Irdha Yusra; Rio Nanda (JURNAL PUNDI, 2019)
AbstractThe purpose of this study was to find out and analyze the effect of product quality, location and price on purchasing decisions at Kinol Bistro N 'Poll Cafe in Padang City. The population in this study were all consumers who made purchases at the Kinol Bistro N ’Poll cafe in Padang City totaling 2,446. while the number of samples in this study were 100 respondents. The sampling technique used is purposive sampling method, namely by taking samples based on certain criteria. Data analysis techniques used to test hypotheses are multiple linear regression, and statistical T test. The results showed that the variables of product quality, price and location had a significant effect on purchasing decisions at Kinol Bistro N 'Poll Cafe in Padang City. Keywords: Product Quality, Location, Price, and Purchasing Decision.